Absence of CD11a Expression Identifies Embryonic Hematopoietic Stem Cell Precursors via Competitive Neonatal Transplantation Assay - Karimzadeh, Alborz; Varady, Erika S.; Scarfone, Vanessa M.; Chao, Connie; Grathwohl, Karin; Nguyen, Pauline U.; Ghorbanian, Yasamine; Weissman, Irving L.; Serwold, Thomas; Inlay, Matthew A. (Frontiers in Cell and Developmental Biology, 2021)
Hematopoietic stem cells (HSCs) are defined by their self-renewal, multipotency, and bone marrow (BM) engraftment abilities. How HSCs emerge during embryonic development remains unclear, but are thought to arise from hemogenic endothelium through an intermediate precursor called “pre-HSCs”. Pre-HSCs have self-renewal and multipotent activity, but lack BM engraftability. They can be identified functionally by transplantation into neonatal recipients, or by in vitro co-culture with cytokines and stroma followed by transplantation into adult recipients. While pre-HSCs express markers such as Kit and CD144, a precise surface marker identity for pre-HSCs has remained elusive due to the fluctuating expression of common HSC markers during embryonic development. We have previously determined that the lack of CD11a expression distinguishes HSCs in adults as well as multipotent progenitors in the embryo. Here, we use a neonatal transplantation assay to identify pre-HSC populations in the mouse embryo. We establish CD11a as a critical marker for the identification and enrichment of pre-HSCs in day 10.5 and 11.5 mouse embryos. Our proposed pre-HSC population, termed “11a- eKLS” (CD11a- Ter119- CD43+ Kit+ Sca1+ CD144+), contains all in vivo long-term engrafting embryonic progenitors. This population also displays a cell-cycle status expected of embryonic HSC precursors. Furthermore, we identify the neonatal liver as the likely source of signals that can mature pre-HSCs into BM-engraftable HSCs.